2021
DOI: 10.1002/solr.202100481
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Pressure Dry Etching of Polysilicon Layers for Highly Reverse Bias‐Stable TOPCon Solar Cells

Abstract: Single‐sided etching (SSE) of a‐Si/poly‐Si is typically considered a challenge for realizing a cost‐efficient TOPCon production sequence, as there is a certain degree of unwanted wrap‐around for poly‐Si deposition technologies such as low pressure chemical vapor deposition, plasma‐enhanced chemical vapor deposition, and atmospheric pressure chemical vapor deposition. To date, alkaline or acidic wet‐chemical solutions in either inline or batch configurations are used for this purpose. Herein, an alternative SSE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…6) Single‐sided gas phase removal of poly‐Si on BBr 3 diffused textured front side. [ 9 ] 7) Wet chemical BSG removal and cleaning. 8) Thermal annealing (800–900 °C).…”
Section: Methodsmentioning
confidence: 99%
“…6) Single‐sided gas phase removal of poly‐Si on BBr 3 diffused textured front side. [ 9 ] 7) Wet chemical BSG removal and cleaning. 8) Thermal annealing (800–900 °C).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Kafle et al have demonstrated that dry etching using an inline-plasma tool results in high parallel resistance and excellent device performance. 106 In this article we are focusing on onesided wet-chemical etching since it is successfully used to remove the parasitic emitter on the back side in large-scale production. Regarding a later gentle removal of the poly-Si wrap-around, it is very useful to leave the borosilicate glass (BSG) on the front emitter in this process step.…”
Section: Removal Of Poly-si Wrap-aroundmentioning
confidence: 99%
“…Various dry and wet processes are known for single‐sided etching of solar cells. Recently, Kafle et al have demonstrated that dry etching using an inline‐plasma tool results in high parallel resistance and excellent device performance 106 . In this article we are focusing on one‐sided wet‐chemical etching since it is successfully used to remove the parasitic emitter on the back side in large‐scale production.…”
Section: Deposition Of Poly‐si Using Pecvdmentioning
confidence: 99%
“…A bifacial TOPCon cell batch with n‐type M2 (156.75 ×156.75 mm 2 ) phosphorous‐doped pseudosquare wafers with a base resistivity of ≈1 Ωcm was processed in cooperation with Fraunhofer ISE following the low pressure chemical vapor deposition in situ poly‐Si route, published by Kafle et al [ 33 ] Deviating from this, the n‐poly‐Si layer deposited on the wafer's front side was removed by dry etching via an atmospheric pressure dry etching (ADE) tool. [ 34 ] Moreover, the wafers got an additional cofiring step before metallization to measure implied V oc . After contact formation in a cofiring step at 800 °C, the wafers were treated with a laser‐enhanced contact formation (LECO) step, to further decrease the series resistance of the contact grids ( R S ).…”
Section: Next‐generation Chemical Edge Isolation For Perc/topconmentioning
confidence: 99%